Macrozoobentos Diversity as A Bioindicator of Water Quality in Poso Lake, South Pamona District, Poso Regency and Its Utilization as A Learning Media - Selvianita Selvianita; Syech Zainal; Bustamim Bustamim (CV. Dharma Samakta Edukhatulistiwa, 2024)
Macrobenthos are animals that live at the bottom of waters, both freshwater and seawater. This study aims to describe the diversity of macrobenthos as a bioindicator of water quality in Lake Poso and its use as a learning medium. This study uses a purposive random sampling method with a sampling technique using free collection with a roaming path method of ± 100 m per station. While the data analysis technique uses quantitative descriptive. The results of the study showed that the macrobenthos diversity index was obtained at station I (2.51) and then followed by station II (2.44) and station III (2.19). While the macrobenthos diversity index in Lake Poso is 2.26 and is categorized as a moderate level of diversity. The high macrobenthos diversity index at station I is because the macrobenthos habitat is still maintained and surrounded by forest vegetation so that the macrobenthos found are quite diverse. The development of research results as a learning media in the form of a pocket book, from the validation results including media validation, content validation, and design validation conducted by 3 expert lecturers and the feasibility test tested on 20 students obtained a percentage of 79.6% and is worthy of being used as a learning media.